Introduction and Basic Calculation Guide Using Ayo Menghitung Application for Early Childhood - Agusniar, Cut; Gemasih, Husna; Zubaedah, Reza (Gameology and Multimedia Expert, 2025)
The advancement of technology in education has enabled the development of various interactive applications that facilitate the learning process, particularly in basic mathematical calculations. The Ayo Menghitung application is designed as a gamification-based learning tool to help children understand the concepts of addition, subtraction, multiplication, division, and number comparison in a more engaging and interactive way. This application features a child-friendly interface and visually appealing elements to enhance user engagement in the learning process. This study aims to develop an educational application that improves children's arithmetic skills through game-based learning methods. The development process includes needs analysis, system design, implementation, and application effectiveness evaluation. The evaluation results indicate that the application successfully increases children's interest in mathematics and helps them understand fundamental arithmetic concepts more effectively. Thus, Ayo Menghitung serves as an innovative solution to support early childhood mathematics education.